2006
DOI: 10.1210/jc.2006-0209
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Functional and Structural Consequences of Two Point Mutations (P94L and A368D) in the CYP11B1 Gene Causing Congenital Adrenal Hyperplasia Resulting from 11-Hydroxylase Deficiency

Abstract: Analyzing the in vitro enzyme function is a complementary procedure to genotyping and a valuable tool for understanding the clinical phenotype of 11-hydroxylase deficiency. This is the basis for accurate genetic counseling, prenatal diagnosis, and treatment. Moreover, the combination of in vitro enzyme function and molecular modeling provides valuable insights in cytochrome P450 structural-functional relationships, although one must be aware of the limitations of in silico-based methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 25 publications
1
31
0
1
Order By: Relevance
“…We found that 41 compound heterozygotes or homozygotes for select missense or nonsense mutations-namely P49L, R141Q, W260X, G267S, L299P, T318M, T318R, A331V, Q356X, A368D, R374Q, V441G, G444D, G446V, and R448H-present with moderate to severe classic CAH because of 11β-hydroxylase, confirming prior results (3,(14)(15)(16)(17)(22)(23)(24). These patients were mainly from Croatia, Tunisia, Africa, Turkey, and Saudi Arabia.…”
Section: Discussionsupporting
confidence: 88%
“…We found that 41 compound heterozygotes or homozygotes for select missense or nonsense mutations-namely P49L, R141Q, W260X, G267S, L299P, T318M, T318R, A331V, Q356X, A368D, R374Q, V441G, G444D, G446V, and R448H-present with moderate to severe classic CAH because of 11β-hydroxylase, confirming prior results (3,(14)(15)(16)(17)(22)(23)(24). These patients were mainly from Croatia, Tunisia, Africa, Turkey, and Saudi Arabia.…”
Section: Discussionsupporting
confidence: 88%
“…Patient 1 is heterozygous for the mutant p.(Arg143Trp), which showed a residual 11b-hydroxylase activity of approximately 8% of wild-type activity, consistent with non-classical 11b-OHD. 12,17,18 The kinetic constants reflect steric changes not necessarily affecting substrate binding but reaction velocity. The residue 143 is located in the C helix with a side chain pointing into the solvent surrounding (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro 11-hydroxylase activity of !5% can be considered severe and is most often associated with classic 11OHD (7,24,40). The patients 1 and 2 carrying a completely inactivating mutation (p.His125Thrfs*8) of the CYP11B1 gene show a typical classical 11OHD phenotype with highly elevated steroids hormones, prenatal virilisation of the external genitalia in females and macrogenitosomia in males (5).…”
Section: Discussionmentioning
confidence: 99%
“…Each mutation was introduced into a CYP11B1-pcDNA3.1 expression vector construct (kindly provided by Prof. R Bernhardt, Institute of Biochemistry, University des Saarlandes, Saarbrücken, Germany) by site-directed mutagenesis as described previously (24,25). In vitro transient transfection assay was performed in triplicates using the HEK293 cell line thrice.…”
Section: Transient Transfection Assaymentioning
confidence: 99%
See 1 more Smart Citation